The mediating role of psychological capital in linking environmental dynamism to entrepreneurial persistence among nascent entrepreneurs in China - Mo, Xiao; Chatpunyakul, Chatchai; Gulthawatvichai, Sarist (My University, 2026)
The paper examines the impact of environmental dynamism on personal outcomes (goal achievement, happiness) and psychological capital (PsyCap) of nascent entrepreneurs through a mediator. A quantitative survey (cross-sectional survey) was done on 136 nascent Chinese entrepreneurs, and regression and mediation analysis were done using SPSS to test hypothesised relationships. The findings indicate that environmental dynamism essentially decreases goal achievement, happiness, and PsyCap, whereas PsyCap is a powerful predictor of these positive results and mediates the relationship between environmental turbulence and personal outcomes, which demonstrates a defensive feature of PsyCap in turbulent environments. In practice, the results highlight the necessity to establish PsyCap through training, mentoring, and incubator assistance and encourage policymakers and educators to supplement financial/institutional interventions with psychological capacity-building. This piece of work is important as it focuses on the individual results of firms rather than companies and emphasises the environmental factors, psychological resources, and well-being to make PsyCap an entrepreneurial sustainability strategic resource.
Keywords: China; entrepreneurial outcomes; environmental dynamism; nascent entrepreneurs; psychological capital